Correlations between track parameters in a solid-state nuclear track detector and its diffraction pattern. (April 2022) - Stevanovic, N.; Markovic, V.M.; Milosevic, M.; Djurdjevic, A.; Stajic, J.M.; Milenkovic, B.; Nikezic, D.
Abstract: Wave optics based theoretical model of light propagation through the track structure in a solid-state nuclear track detector was developed in this article. When coherent and monochromatic light passes through the track structure, diffraction rings are formed around track opening. The distribution of the light intensity (diffraction pattern) from the post-etched detector surface depends on the track shape and dimensions, or indirectly on the incident alpha particle energy and removed layer during the etching. In this article authors established correlations between parameters of diffraction pattern and incident alpha particle energy for standardized etching conditions. Criteria for applicability of geometric optics is introduced, and it was shown that for some cases use of wave optic is necessary. Highlights: Model of light propagation through track surface was presented. Diffraction pattern of light was presented. Correlation of diffraction pattern and alpha particle energy was established. Experimental confirmation of presented model was done.